Assistance of Students in Detecting The Risk of Transmission of COVID-19 - Lindawati, Lindawati; Fadmawati, Ani (POLTEKKES KEMENKES BANTEN, 2023)
Early detection of Covid-19 transmission is an effort to suppress the spread of Covid-19. Ministry of Education and Culture, (2021) the transmission of Covid-19 infection now is school children, students who live in dormitories or orphanages so that a new cluster of Covid transmission appears as a result of not implementing health protocols with discipline. In addition, there is a lack of correct knowledge about the dangers of Covid-19, revention and the ability to detect infection or the risk of being exposed to Covid-19. One of the groups that is very at risk of being infected with Covid-19 is the students of the Nurul Jadid Orphanage, for this reason assistance is needed in early detection of the risk of transmission. Covid-19 to suppress the spread of Covid-19 in the surrounding environment. The purpose of this community service is to increase the knowledge and ability of the students and orphanage caretakers in detecting symptoms of infection and the risk of being infected with Covid19. The method of service is to provide counseling about Covid-19 and detect the risk of transmission of Covid19. The results obtained were an increase in knowledge for 15 students who attend these activities and students are able to carry out early detection of the risk of transmission of Covid-19.